HDL from 36-h fasted participants potently promotes efflux of cholesteryl ester from activated microglia - Agus, Joanne K.; Muñoz Herrera, Oscar M.; Rhodes, Christopher H.; Zheng, Jack Jingyuan; Zhu, Chenghao; Wong, Maurice; Tang, Xinyu; Maezawa, Izumi; Jin, Lee-Way; Lebrilla, Carlito B.; Harvey, Danielle J.; Zivkovic, Angela M. (Frontiers in Aging Neuroscience, 2025)
The potential impact of lifestyle changes such as prolonged fasting on brain health still remains unclear. Neurodegenerative diseases often exhibit two key hallmarks: accumulation of misfolded proteins such as amyloid beta oligomers (AβO) and intracellular cholesterol accumulation. In this study, we investigate how a 36-h fast affects the capacity of isolated high-density lipoproteins (HDLs) to modulate the effects of AβO and excess cholesterol in microglia. HDL from 36-h fasted individuals were significantly more effective in effluxing cholesteryl esters from treated microglia, showing a remarkable 10-fold improvement compared to HDL from the postprandial state. Furthermore, the ability of 36-h fasted HDL to mitigate the reduction of apolipoprotein E secretion in AβO- and cholesterol-loaded microglia surpassed that of postprandial HDL. In exploring differences among HDL parameters from postprandial, overnight fasted, and 36-h fasted individuals, we observed that plasma HDL-cholesterol and apolipoprotein A-I concentrations remained unchanged. However, nuclear magnetic resonance (NMR) analysis revealed reduced total HDL particle count, a decrease in the smallest HDL particles (HDL1, 7.4 nm diameter), and an increase in the largest HDL particles (HDL7, 12 nm) after the 36-h fast. Transmission electron microscopy (TEM) analysis further found an increase in even larger HDL particles (12–14 nm) in 36-h fasted individuals. Targeted mass spectrometry (MS)-based proteomics and glycoproteomics unveiled a reduction in HDL-associated apolipoprotein A-IV and disialylated apolipoprotein C-III content following the 36-h fast. These findings collectively suggest that prolonged fasting induces structural, compositional, and functional alterations in HDL particles, and influences their capacity to attenuate the effects of excess cholesterol and AβO in microglia.